Effects of Bacillus subtilis on the immune parameters, intestinal morphology and mucin gene expression in broilers exposed to Salmonella enterica challenge - Jouybari, MG; Sadeghi, AA; Jouzani, GS; Chamani, M; Aminafshar, M (Journal of the Hellenic Veterinary Medical Society, 2024)
The objective of this study was to evaluate the effect of the probiotic Bacillus subtilis supplementation on bacterial population, morphometry and mucin gene expression of intestine, and on immune response in Salmonella challenged broilers. Treatments were: 1) negative control (no probiotic- no challenging); 2) probiotic treated (no challenging); 3) positive control (no probiotic-salmonella challenging), and 4) Salmonella challenged chicks fed probiotic. Salmonella infection resulted in significant decrease in the relative weight of thymus. In challenged birds, dietary addition of probiotic increased (P<0.0.5) the relative weights of bursa and thymus. Population of lactic acid bacteria was significantly higher in probiotic treated groups as compared to negative control or challenged chickens. Challenged chickens had the lowest count of goblet cells and those received probiotic had the highest goblet cells count. The expression of mucin 2 gene was higher in group received dietary probiotic as compared with other treatments. Difference for gene expression was not found in challenged chickens and the negative control (P>0.05). In conclusion, the dietary inclusion of Bacillus subtilis could alleviate the negative effects of Salmonella infection on intestinal cells and bacterial population and could improve the growth and development of immune organs and function in infected broilers.